A Serum Pharmacochemistry and Network Pharmacology-based Approach to Study the Anti-depressant Effect of Chaihu-Shugan San - Deng, Man-Fei; Yan, Yi-Zhi; Zhu, Shan-Shan; Zhou, Ke; Tan, Si-Jie; Zeng, Peng (Combinatorial Chemistry & High Throughput Screening, 2025)
AimsThe aim of this study is to explore the anti-depressant mechanism of Chaihu-Shugan San based on serum medicinal chemistry and network pharmacology methods.BackgroundDepression lacks effective treatments, with current anti-depressants ineffective in 40% of patients. Chaihu-Shugan San (CHSGS) is a well-known traditional Chinese medicine compound to treat depression. However, the chemical components and the underlying mechanisms targeting the liver and brain in the anti-depressant effects of CHSGS need to be elucidated.MethodsThe chemical components of CHSGS in most current network pharmacology studies are screened from TCMSP and TCMID databases. In this study, we investigated the mechanism and material basis of soothing the liver and relieving depression in the treatment of depression by CHSGS based on serum pharmacochemistry. The anti-depressant mechanism of CHSGS was further verified by proteomics and high-throughput data.ResultsThrough serum medicinal chemistry, we obtained 9 bioactive substances of CHSGS. These ingredients have good human oral bioavailability and are non-toxic. Based on liver ChIP-seq data, CHSGS acts on 8 targets specifically localized in the liver, such as FGA, FGB, and FGG. The main contributors to CHSGS soothing the liver qi targets are hesperetin, nobiletin, ferulic acid, naringin and albiflorin. In addition, network pharmacology analysis identified 9 blood components of CHSGS that corresponded to 63 anti-depressant targets in the brain. Among them, nobiletin has the largest number of anti-depressant targets, followed by glycyrrhizic acid, ferulic acid, albiflorin and hesperetin. We also validated the anti-depressant mechanism of CHSGS based on hippocampal proteomics. CHSGS exerts anti-depressant effects on synaptic structure and neuronal function by targeting multiple synapse related proteins.ConclusionThis study not only provides a theoretical basis for further expanding the clinical application of CHSGS, but also provides a series of potential lead compounds for the development of depression drugs.
Keywords: anti-depressant effect